2022
DOI: 10.21608/aujes.2022.121974.1059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date on Productivity of Some Sugar Beet Varieties Under Kom Ombo Conditions.

Abstract: A field experiment was carried out at Kom-Ombo Agricultural research Station Farm, (latitude of 24 o 28′ N and longitude of 32 o 57′ E), Aswan Governorate, during 2019-2020 and 2020-2021 seasons to study the effect of sowing dates on growth, technological and yield traits of some sugar beet varieties under Kom Ombo conditions. Randomized complete lock design (RCBD) using a strip plot arrangement with three replications were used. Planting dates (30 th September, October 15 th and 30 th October) were allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Research by Harris (2015), Sah et al (2016), andLi et al (2017), has shown that abscisic acid regulates the growth of primary roots and the branching of lateral roots in plants. These results are in line with those of Awadalla et al (2022), who discovered that during the two seasons, the tested sugar beet cultivars significantly influenced the root diameter trait.…”
Section: Productivity Traitssupporting
confidence: 92%
See 1 more Smart Citation
“…Research by Harris (2015), Sah et al (2016), andLi et al (2017), has shown that abscisic acid regulates the growth of primary roots and the branching of lateral roots in plants. These results are in line with those of Awadalla et al (2022), who discovered that during the two seasons, the tested sugar beet cultivars significantly influenced the root diameter trait.…”
Section: Productivity Traitssupporting
confidence: 92%
“…The sugar beet Shantala-KWS variety recorded the highest values of sucrose % and TSS%, as did the Husam variety in TSS%. Awadalla et al (2022) found that the tested sugar beet cultivars, varieties, or genotypes had a significant effect on the sucrose trait in both seasons. Concerning the effect of ABA, the result in Table 4 revealed that the highest values of sucrose % and TSS% of sugar beet root were recorded with ABA at 3000 ppm, while the lowest ones were recorded with control treatments (water spray).…”
Section: Quality Traitsmentioning
confidence: 89%
“…Sunflower stood at second rank to soybean for production and extraction of edible oil in the world. The sunflower oil signifies approximately 15 percent of the world oil production (Ahmed et al,2023).…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower as a non-traditional crops has the potential to close the breach between national production and edible oil import. Oil contents of 25-48% and protein contents of 20-27% are present in seed of sunflower (Ahmed et al,2023). Sunflower oil is delicious and high in A, D, E, and K vitamins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation